Comparative evaluation of remineralizing efficacy of biomimetic self-assembling peptide on artificially induced enamel lesions: an in vitro study - Kamal, Dina; Hassanein, ElHassan; Elkassas, Dina; Hamza, Heba (Journal of conservative dentistry, 2018)
Background: The biomimetic self-assembling peptide technology is a paradigm for dental hard tissue regeneration. Aim: To investigate the efficacy of biomimetic self-assembling peptide (P11-4) on enamel remineralization compared to casein phosphopeptide-amorphous calcium phosphate fluoride (CPP-ACPF) and fluoride-based delivery systems. Materials and Methods: Artificial enamel lesions were created on buccal surfaces of 40 extracted human molars. Specimens were randomly assigned to four groups (n = 10) according to the remineralizing agent used: G1 - control: artificial saliva, G2 - fluoride varnish, G3 - CPP-ACPF varnish, G4 - self-assembling peptide agent. All products were applied according to the manufacturer's instructions and the specimens were stored in daily renewed artificial saliva. Surface microhardness (SMH) was assessed at baseline, after demineralization, after 1 week and after 4 weeks storage. SMH values were analyzed using ANOVA and Tukey's post hoc test. Results: Self-assembling peptide showed the highest statistically significant mean SMH followed by fluoride and CPP-ACPF while the lowest mean SMH was found in artificial saliva. However, no statistically significant difference was found between fluoride and CPP-ACPF. Higher statistically significant mean SMH was found after 4 weeks compared to 1 week remineralization in all groups. Conclusions: Self-assembling peptide confers the highest remineralizing efficacy compared to fluoride and CPP-ACPF, showing a promising, noninvasive regeneration potential. Furthermore, extended period of time helped attain more benefits from the remineralizing regimens applied.